Diagnóstico das casas de farinha da associação de produtores da agrovila Nazaré, Castanhal-PA - SANTOS, Rayssa Silva dos (Instituto Federal de Educação, Ciência e Tecnologia do Pará, 2023)
Cassava flour, highly appreciated by the Brazilian population, has a wide and diversified consumption. The production of this derivative must meet the hygiene requirements stipulated by the legislation governing food-producing establishments to ensure its quality. Thus, this study aimed to evaluate the hygienic and sanitary conditions of flour houses located in Agrovila Nazaré and surrounding region, whose producers are associated with the Agrovila Nazaré Residents and Farmers Association, and to propose improvements in accordance with Good Manufacturing Practices (GMP). For this, the hygienic-sanitary diagnosis was made using the checklist of good manufacturing practices, document attached to RDC No. 275/2002, with modifications, and the establishment with the lowest percentage of adequacy and highest monthly production was selected to perform the physical characterization -chemical and microbiological of the flour produced and train producers in GMP. Aiming to obtain more information about the community under study, the socioeconomic diagnosis of the producers was also carried out using a structured questionnaire with open and closed questions of socioeconomic, productive, environmental and issues related to GMP. The results were tabulated and analyzed using Microsoft Excel software. It was found that the evaluated flour houses have a low percentage of adequacy, classifying them in group 3, from 0 to 50% of attendance of the evaluated items, a fact that may be related to the little knowledge of producers regarding this quality tool. The results of the physicochemical and microbiological analyzes of the flour samples collected in the selected project showed that most of the parameters evaluated were in accordance with the technical regulation of the product, with the exception of starch, crude fiber, bark and bark and foreign matter. The presence of foreign matter highlights the need to implement improvements in the infrastructure of the establishment and, for this, suggestions were made to the owner and a proposal for the floor plan of a flour house was prepared with the requirements stipulated in the legislation and delivered to the producer. In the socioeconomic diagnosis, it was observed that the production of flour constitutes the main income for most of the interviewees and that they have, for the most part, low education. It was also noted the need to improve access to basic sanitation and provide guidance on the correct disposal of manipueira. It was found that the performance of the association which the interviewed producers are part of is satisfactory, as it meets their needs, but they need to implement more actions aimed at marketing the flour. The implementation of GMP during the production of flour ensures its quality and makes it possible to adapt and regularize the enterprise, as well as access to new markets, generating improvements in the living conditions of farmers and stimulating development in rural areas.